Does minimal central nervous system involvement in childhood acute lymphoblastic leukemia increase the risk for central nervous system toxicity?. Issue 7 (30th April 2022) - Anastasopoulou, Stavroula; Harila‐Saari, Arja; Als‐Nielsen, Bodil; Eriksson, Mats Anders; Heyman, Mats; Johannsdottir, Inga Maria; Marquart, Hanne Vibeke; Niinimäki, Riitta; Pronk, Cornelis Jan; Schmiegelow, Kjeld; Vaitkeviciene, Goda; Thastrup, Maria; et al.
Abstract: Central nervous system (CNS) involvement in childhood acute lymphoblastic leukemia (ALL) implicates enhanced intrathecal chemotherapy, which is related to CNS toxicity. Whether CNS involvement alone contributes to CNS toxicity remains unclear. We studied the occurrence of all CNS toxicities, seizures, and posterior reversible encephalopathy syndrome (PRES) in children with ALL without enhanced intrathecal chemotherapy with CNS involvement ( n  = 64) or without CNS involvement ( n  = 256) by flow cytometry. CNS involvement increased the risk for all CNS toxicities, seizures, and PRES in univariate analysis and, after adjusting for induction therapy, for seizures (hazard ratio [HR] = 3.33; 95% confidence interval [CI]: 1.26–8.82; p  = 0.016) and PRES (HR = 4.85; 95% CI: 1.71–13.75; p  = 0.003).